Exploring patient views of empathic optimistic communication for osteoarthritis in primary care: a qualitative interview study using vignettes. Issue 3 (June 2021) - Lyness, Emily; Vennik, Jane Louise; Bishop, Felicity L; Misurya, Pranati; Howick, Jeremy; Smith, Kirsten A; Ratnapalan, Mohana; Hughes, Stephanie; Dambha-Miller, Hajira; Bostock, Jennifer; Morrison, Leanne; Mallen, Christian D; et al.
No abstract available